HUBUNGAN KARAKTERISTIK INDIVIDU TERHADAP TINGKAT KECEMASAN PEMERIKSAAN SWAB ANTIGEN COVID-19 PADA MASYARAKAT RT.04 RW.01 KAMPUNG BAKUNG - Fauziah, Anisya Nur; Sriningsih, Nining; Septimar, Zahrah Maulidia (Nusantara Hasana Journal, 2022)
In Indonesia, the first Covid-19 case was confirmed on March 2, 2020, a total of two cases (Nuraini, 2020) it was stated that during the pandemic, all arrangements for carrying out this covid test had to be carried out. Antigen Swab. This examination caused a lot of anxiety in the community, both male and female individuals, work, education on March 3, 2020, 90,870 confirmed cases and 3,112 cases of death were also still occurring. although balanced by the number of patients recovering. Globally, there are 198,010,967 cases of covid-19 with 4,224,124 deaths (Kemenkes RI, 2020) on March 3, 2020, 90,870 confirmed cases and 3,112 cases of death also continued to occur even though it was offset by the number of recovered patients. Globally, there are 198,010,967 cases of COVID-19 with 4,224,124 deaths Research Objectives: Knowing the relationship between individual characteristics and the anxiety level of the COVID-19 antigen swab examination. Methods: The sampling technique in this study used accidental sampling, the research sample of the community who attended was 114 respondents. Research Design: chi-square test results. The relationship between individual characteristics Age p-value = 0.027, gender p-value = 0.032, education p-value 0.037, work p-value 0.001 because the value of sig < 0.05 means that it can be concluded that there is a relationship between individual characteristic variables and the level of anxiety of the swab examination Covid-19 antigen in the community of the daffodil village Rt 004 Rw 001. Conclusions and suggestions: The results of the study showed that there was a relationship between individual characteristics and the anxiety level of the COVID-19 antigen swab examination.